Potensi Penyerapan Karbon Pada Sistem Agroforestri Di Desa Pesawaran Indah Kecamatan Padang Cermin Kabupaten Pesawaran Provinsi Lampung - Dessy Natalia; Slamet Budi Yuwono; Rommy Qurniati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
This research aims to determine dominant vegetation and amount of carbon absorption of agroforestry systems.This research held at Pesawaran Indah Village, Padang Cermin Sub Distric, Pesawaran Distic, Lampung Province on April - June 2012. It is used Summed Dominance Ratio (SDR) methode, vegetation of INP (Indeks Nilai Penting) and than to calculate the carbon absorption by allometrik equation. Agroforestry land lies on fisiography category.There are three fisiography to ease in obtaining the data. There are low land, middle land, up land and forest hamlet. On low land the dominanat vegetation for tree phase is Teak (Tectona grandis), and for pole, sapling and seedling phase is dominant Cacao (Theobroma cacao).On middle land the dominanat vegetation for tree phase is Avocado (Persea americana), the pole, sapling and seedling phase is dominant Cacao (Theobroma cacao).On up land the dominant vegetation for tree phase is Waru (Hibiscus macrophyllus), the pole, sapling and seedling phase is dominant Cacao (Theobroma cacao). On village forest the dominant vegetation for tree phase is Taboos (Crescentia pujeta), pole phase is Champaca (Michelia champaca), sapling phase is Bamboo (Gigantochloa apus) and seedling phase is hevea (Hevea brasiliensis). The results of carbon above absorption on agroforestry lands at Pesawaran Indah Village is 118,96 Mg/ha (low land), 104,16 Mg/ha (Middle land) and 89,01 Mg/ha (up land) and 526,43 Mg/ha (forest hamled). Keywords: agroforestry, carbon, dominant vegetation